2018
DOI: 10.1557/jmr.2018.362
|View full text |Cite
|
Sign up to set email alerts
|

Chain rotation significantly reduces thermal conductivity of single-chain polymers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 38 publications
1
35
0
1
Order By: Relevance
“…These results suggest that improving the chain alignment along the thermal transport directions is an effective way to enhance the thermal conductivity of polymers. Moreover, Ma and Tian have studied the role of the chain rotation on thermal conductivity of single‐chain polymers by molecular dynamics simulations. The authors found that large chain rotations can reduce the phonon group velocities, resulting in the reduction of thermal conductivity.…”
Section: Manipulation Of Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that improving the chain alignment along the thermal transport directions is an effective way to enhance the thermal conductivity of polymers. Moreover, Ma and Tian have studied the role of the chain rotation on thermal conductivity of single‐chain polymers by molecular dynamics simulations. The authors found that large chain rotations can reduce the phonon group velocities, resulting in the reduction of thermal conductivity.…”
Section: Manipulation Of Thermal Conductivitymentioning
confidence: 99%
“…These results suggest that improving the chain alignment along the thermal transport directions is an effective way to enhance the thermal conductivity of polymers. Moreover, Ma and Tian [132] have Adv. Funct.…”
Section: Alignment Of Chain Orientationsmentioning
confidence: 99%
“…Meanwhile, Ma et al investigated the reduced thermal conductivity of the polymer. The effects of chain rotation on the thermal conductivity of a single chain polymer derived from poly(2,2′‐disulfonyl‐4,4′‐benzidine terephthalamide) (PBDT) derivatives and Kevlar using the equilibrium molecular dynamics method were investigated . They found that chain rotation played a necessary role in reducing the thermal conductivity in a given polymer chain from stretched to unstretched or between different polymer chains.…”
Section: Thermal Conduction Of Pcmsmentioning
confidence: 99%
“…The effects of chain rotation on the thermal conductivity of a single chain polymer derived from poly(2,2′-disulfonyl-4,4′-benzidine terephthalamide) (PBDT) derivatives and Kevlar using the equilibrium molecular dynamics method were investigated. [147] They found that chain rotation played a necessary role in reducing the thermal conductivity in a given polymer chain from stretched to unstretched or between different polymer chains. It was found that the functional groups on benzene rings in single-chain polymers derived from PBDT derivatives were critical to chain rotation.…”
Section: Thermal Conductivity Reduction Of Pcmsmentioning
confidence: 99%
“…Liao et al found that the thermal conductivity of aligned PE-CNT nanocomposites can reach 60 W m −1 K −1 [22], and the heavy atoms can impede phonons transport along PE chain [23]. Ma et al demonstrated that the redundant side chains [24] and chain rotation [25] can reduce phonon mean free path. They also developed a theoretical model related to bond energy, backbone rotation, in-plane bond ratio, and atomic amass to predict thermal conductivity of crystalline polymers [26].…”
Section: Introductionmentioning
confidence: 99%